Development of knowledge management infrastructure in organization - N.I. Sytnik (Marketing i Menedžment Innovacij, 2016)
The aim of the article. The aim of the article is to analyze development of knowledge management infrastructure (KM infrastructure) at various stages of knowledge management evolution at organization. The results of the analysis. KM infrastructure is an important issue of the improvement of existing knowledge management systems. KM infrastructure could be defined as a set of interrelated organizational factors that ensure long-term operation and development of KM and support organizational processes of knowledge capture, share, accumulation, transfer, and use. Theoretically the concept of KM infrastructure is close to the concept of «ba» – enabling context, space, conditions needed to manage knowledge flows effectively. However, these concepts are not identical and the differences between them are highlighted and discussed in the study. Content analysis of the academic literature devoted to KM provision allowed determining major components of well-developed KM infrastructure. It consists of common knowledge, physical space, human resources management procedures, IT, organizational structure and culture. Their specific roles in KM functioning are discussed. It is shown that KM evolution at organization is associated with the development of corresponding KM infrastructure. At the spontaneous stage employees exchanged data and information on demand and knowledge processes were rather sporadic and badly organized. KM infrastructure incorporated mainly common knowledge (in tacit form) and physical space for job-related communications between employees. Growing awareness of knowledge value at high management levels leaded to development of human resources management procedures specific to KM processes support. These procedures were directed mainly at accumulation of personal knowledge through vocational training and enhancing organizational knowledge basis through recruitment of highly qualified employees. The attempts to codify and store valuable information were intensified as well. Next stage in KM development was related to revolutionary growth in opportunities to store, share and transfer explicit knowledge caused by wide-spread usage of information technologies (IT). Sophisticated IT tools became an important component of KM infrastructure although IT did not meet managers’ expectations in terms of cost-result ratio to full extent. The next social and behavioral stage in KM development is characterized by shifting the focus of managers attention to the broad range of social factors vitally needed to support generation, share, transfer and use of both tacit and explicit knowledge. Organizational culture is recognized as crucial enabler of organizational knowledge processes and the most important component of KM infrastructure. At the integration stage KM is seen to be embedded totally in innovation management system providing permanent business renewal and competitiveness with all components of KM infrastructure reaching high levels of their development. Conclusions and directions for future research. The evolution of KM systems associated with corresponding development of KM infrastructure. The transition to higher KM stages is accompanied by an increase in the number of KM infrastructure components involved as well as by their complication and enhancement. Further researches in this area should be aimed at discovering the impact of essential organizational features (business area, strategic goals, size etc.) on KM infrastructure development.